2015
DOI: 10.9710/kjm.2015.31.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Stocking Density of 3-year-old Pacific Abalone, Haliotis discus hannai Reared in Net Cage Culture

Abstract: The effects of different stocking densities on the growth and survival rate of the 3-year-old pacific abalone, Haliotis dicus hannai were investigated in marine net cage for a year. Stocking densities in net cage (2.4 × 1.2 m) was set 15, 30, 45 and 60 percentage (= per)/sq m (square meter, m 2 ) with share to cross-sectional area per shelter. The water temperature during the testing period was 8.2℃-22.1℃, and salinity is 33.5 ± 0.6 psu, and dissolved oxygen is 7.87 ± 0.86 mg/L. In the shell length (initial si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…T. sazae is a sub-tropical species found in subtidal habitats with water temperatures of 14 • C to 25 • C [35,37], which suggests that it can withstand higher temperatures than M. nudus. In our study, it showed a gradual increase in the food consumption rate with an increase in temperature, with a peak at 25 • C. In such gastropods, increases in temperature lead to higher metabolic demand, thus increasing food consumption [59][60][61][62]. For example, the rate of Turbo samaticus gradually increases with increasing temperature, peaking at 25 • C [63]; in Haliotis midae, the rate doubles at 15 • C compared to 22 • C [64].…”
Section: Discussionsupporting
confidence: 50%
“…T. sazae is a sub-tropical species found in subtidal habitats with water temperatures of 14 • C to 25 • C [35,37], which suggests that it can withstand higher temperatures than M. nudus. In our study, it showed a gradual increase in the food consumption rate with an increase in temperature, with a peak at 25 • C. In such gastropods, increases in temperature lead to higher metabolic demand, thus increasing food consumption [59][60][61][62]. For example, the rate of Turbo samaticus gradually increases with increasing temperature, peaking at 25 • C [63]; in Haliotis midae, the rate doubles at 15 • C compared to 22 • C [64].…”
Section: Discussionsupporting
confidence: 50%